Desapropriação indireta - Cascaldi, Marcela Sproesser (2019)
This essay aims to analyze the Indirect Expropriation, a procedure through which the Administration improperly and irregularly takes possession of the private property, especially its constitutionality, considering that expropriation is one of the most severe forms of State intervention in private property, constitutionally authorized provided that the required guarantees and formalities are observed. Therefore, the present study is based on qualitative research, carried out by deductive method, through an analysis of doctrine, legislation, jurisprudence and constitutional principles. We begin with the study of property, its legal delimitation, the historical evolution of the concept and the subordination to the principle of the “social function of property”. Next, we analyze the relation between this principle with the State's forms of intervention in the private property, specially the expropriation, it´s concept and legal treatment, its requirements, as well as the species of expropriation provided by the Federal Constitution of Brazil. We then proceed to the study of indirect expropriation, its concept and legal basis, its species, the action of the injured party to be compensated for the damages caused by the Administration, as well as the effects resulting from expropriation. Finally, we conclude that the indirect expropriation is unconstitutional, considering that it is a manifestly unlawful act of the Public Power, which violates the property right without observing due process of expropriation, disregarding the formalities inherent to the institute, especially the payment of joust and prior indemnification in cash and that should lead to civil, administrative and criminal punishment of the political and administrative agents responsible for the unlawfulness